Kontrola realizacji strategii stacji radiowej w obszarze programowym - Kotapski, Roman (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2005)
Planning of the radio programme and broadcast are very important. The strategy of the radio broadcasting station influences for choice, the radio programme index. The system proposition of the radio programme index is written at this article. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1080, s. 137-146